Characteristics of chronic rhinosinusitis patients at the ENT head and neck polyclinic - Kristina, Yemima; Lubis, Yuliani Mardiati; Tambunan, Andika Zayani; Rezeki, Naomi Grace (Institute of Computer Science (IOCS), 2025)
Background: Chronic rhinosinusitis (CRS) is a long-lasting inflammatory disorder affecting the nasal passages, paranasal sinuses, and upper respiratory tract, marked by symptoms persisting for a minimum of 12 weeks. The purpose of this study is to identify the characteristics of chronic rhinosinusitis patients at the ENT Head and Neck Polyclinic at ROYAL PRIMA Hospital, Medan. Methods: A descriptive research design with a retrospective data collection method was used through secondary data. The population comprised medical records of patients diagnosed with chronic rhinosinusitis at the outpatient polyclinic during the 2021-2022 period, totaling 80 records. Data were collected using purposive sampling, selecting the most complete medical records. Results: The distribution of chronic rhinosinusitis patients showed that the largest age group was 20-29 years (28.4%). Females were more affected (59.7%) than males (40.3%). The most common primary complaint was nasal congestion (28.4%), with the maxillary sinus being the most infected (47.8%). Medical treatment was predominant (55.2%) compared to surgical intervention (turbinectomy) at (44.8%), emphasizing the need for patient evaluation to ensure appropriate treatment. Conclusions: This study provides an overview of chronic rhinosinusitis (CRS) patients, highlighting that those aged 20-29 years are most affected, with a notable prevalence among females (59.7%). The primary complaints include nasal obstruction, facial pain, and headaches, often linked to inflammation and blockage in the sinus pathways. Treatment typically involves pharmacological therapy, while surgery is reserved for those with more severe cases, emphasizing the need for tailored management strategies.